Nitric oxide affects cadmium-induced changes in the lichen Ramalina farinacea - Kováčik, Jozef; Dresler, Sławomir; Micalizzi, Giuseppe; Babula, Petr; Hladký, Juraj; Mondello, Luigi (Nitric oxide, 2019)
Metabolic responses of epiphytic lichen Ramalina farinacea to cadmium (Cd) and/or nitric oxide (NO) scavenger (cPTIO) were studied. Accumulation of Cd and other metallic nutrients was not affected by cPTIO while total and absorbed amounts differed. Cd-induced NO formation was suppressed by cPTIO but ROS signal was synergistically enhanced, confirming that NO is essential to keep ROS under control. This excessive ROS generation could be a reason for depleted amount of all fatty acids, including SFAs, MUFAs and PUFAs. Total content of fatty acids reached 3.89 mg/g DW in control with linoleic (40%), palmitic (24%), oleic (12.8%) and stearic (8%) acids as major compounds: interestingly, shift in relative ratio of saturated (from 40 to 35% of total FAs) versus polyunsaturated fatty acids (from 42 to 48% of total FAs) was observed. Glutathione was suppressed by all treatments but Krebs acids were almost unaffected by cPTIO, indicating no regulatory role of NO in their accumulation. On the contrary, Cd-induced elevation in NO signal was related to increase in ascorbate and proline content while cPTIO suppressed it, indicating a tight relation between NO and these metabolites. Data are compared also with algae and vascular plants to show similarities between various life lineages.
Keywords: scavengery volných radikálů; Lichens; lišejníky; Cadmium; oxid dusnatý; Free Radical Scavengers; Nitric Oxide; Microscopy, Fluorescence; kadmium; fluorescenční mikroskopie